Streetwise : a psychological analysis of the lives of street children, implications for reintegration into the society - Mako, Maletse Kiddo (My University, 2000)
Refer to document
Thesis (Ph.D. (Clinical Psychology)) -- University of Limpopo, 2000
Keywords: Clinical psychology; Homeless children; Street children; Psychology -- Research